The truth about Barcelona : Official information from the CNT : Stalinist sabotage of unity - Confederación Nacional del Trabajo (Spain) (Glasgow : Anti-Parliamentary Volunteers)
1937-05 SA14-003-013 15 pages : illustrations ; 21 cm. 15X/2/24/1